2002
DOI: 10.1097/01.lab.0000029148.88524.ce
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Binding to Fas Ligand Attenuates Inflammatory Cell Infiltration and Cytokine Secretion, Leading to Reduction of Myocardial Infarct Areas and Reperfusion Injury

Abstract: SUMMARY: Fas ligand (FasL) induces apoptotic cell death when bound to Fas antigen. The engagement of FasL hasanti-inflammatory effects through the prevention of cell proliferation and cytokine secretion. However, the role of FasL in myocardial ischemia/reperfusion (MI/R) injury is unclear. We examined the expression of FasL mRNA in the myocardium of MI/R rats by ligating the left coronary artery for 30 minutes and allowing reperfusion to occur for 0, 1, 3, and 24 hours. The expression of FasL mRNA was enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…21 Moreover, FasL cross-linking leads to recruitment of neutrophils and increased inflammation, 12 and FasL deficiency attenuates inflammatory cell infiltration and cytokine secretion. 11,22 However, overexpression of FasL in dendritic cells decreased allergen-specific T cells and airway inflammation. 15,25 Studies on the effects of FasL in IRI have also produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Moreover, FasL cross-linking leads to recruitment of neutrophils and increased inflammation, 12 and FasL deficiency attenuates inflammatory cell infiltration and cytokine secretion. 11,22 However, overexpression of FasL in dendritic cells decreased allergen-specific T cells and airway inflammation. 15,25 Studies on the effects of FasL in IRI have also produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…15,25 Studies on the effects of FasL in IRI have also produced conflicting results. [22][23][24][25] FasL expression was increased in infiltrating neutrophils and T lymphocytes after renal IRI; 28 however, little is known about their role in AKI after IRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fas is best known for its involvement in the regulation of apoptosis, Fas ligation also contributes to activation of NF-B (Ponton et al, 1996), and it has been shown that interruption of Fas/FasL signaling suppressed NF-B activation and cytokine expression (Shiraishi et al, 2002). We recently showed that NF-B activation and production of proinflammatory cytokines were suppressed in sFas transgenic mice (Niu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41] Although not fully established, factors evident in atherosclerotic lesions can influence the expression of these death receptors and their ligands (Table 2), and some of these factors include TNF-␣ itself, insulin, oxLDL, IFN family members, homocystein, IL-1, and NFB. Increased or decreased expression of TNFR or TNF ligands may contribute to their physiological role to induce death or survival of cells; however, vascular cells are frequently resistant to TNFRmediated death.…”
Section: Role Of Death Receptors In the Vasculaturementioning
confidence: 99%